2018
DOI: 10.1115/1.4041595
|View full text |Cite
|
Sign up to set email alerts
|

Li-Ion Battery Pack Thermal Management: Liquid Versus Air Cooling

Abstract: The Li-ion battery operation life is strongly dependent on the operating temperature and the temperature variation that occurs within each individual cell. Liquid-cooling is very effective in removing substantial amounts of heat with relatively low flow rates. On the other hand, air-cooling is simpler, lighter, and easier to maintain. However, for achieving similar cooling performance, a much higher volumetric air flow rate is required due to its lower heat capacity. This paper describes the fundamental differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…On the other hand, in hybrid vehicles and 100% electric vehicles with high battery power demand, the most widespread system is liquid cooling due to the ability to keep the battery at the ideal temperature even in situations of extreme battery usage and high heat release. In a comparative assessment carried out by Han et al [15], it was demonstrated that while the liquid cooling system has a rating of 500 W/K, the air-cooling system is around 70 W/K.…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in hybrid vehicles and 100% electric vehicles with high battery power demand, the most widespread system is liquid cooling due to the ability to keep the battery at the ideal temperature even in situations of extreme battery usage and high heat release. In a comparative assessment carried out by Han et al [15], it was demonstrated that while the liquid cooling system has a rating of 500 W/K, the air-cooling system is around 70 W/K.…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
“…High thermal conductivity, mostly applied for high cooling demand [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. complexity, high cost, heavy, must store the fluid, viscosity, potential leaks, additives for anti-freeze & Boiling [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…Here and in the following, T F1 = T F1,I . The symbol T M,∞ denotes the temperature of the surroundings of the specific component M. This temperature can be assumed to be equal to the mean value of the inflowing and effluent cooling liquid temperature [20].…”
Section: B Thermal Modelsmentioning
confidence: 99%
“…The low heat air capacity causes its temperature to rise when used to cool series-connected cells. Thus, the outermost cells are not well cooled, leading to an uneven temperature distribution [9]. These limitations can be addressed by taking some measurement when building the battery pack, such as the battery size and the arrangement of the cells.…”
Section: Introductionmentioning
confidence: 99%